DLSR: a solution to the parallax artefact in X‐ray diffraction computed tomography data. Issue 6 (20th November 2020) - Vamvakeros, A.; Coelho, A. A.; Matras, D.; Dong, H.; Odarchenko, Y.; Price, S. W. T.; Butler, K. T.; Gutowski, O.; Dippel, A.-C.; Zimmermann, M.; Martens, I.; Drnec, J.; et al.
Abstract : A new reconstruction approach is presented that can directly yield physico‐chemical images and overcome the parallax problem in X‐ray diffraction computed tomography experiments. Abstract : A new tomographic reconstruction algorithm is presented, termed direct least‐squares reconstruction (DLSR), which solves the well known parallax problem in X‐ray‐scattering‐based experiments. The parallax artefact arises from relatively large samples where X‐rays, scattered from a scattering angle 2gθ, arrive at multiple detector elements. This phenomenon leads to loss of physico‐chemical information associated with diffraction peak shape and position ( i.e. altering the calculated crystallite size and lattice parameter values, respectively) and is currently the major barrier to investigating samples and devices at the centimetre level (scale‐up problem). The accuracy of the DLSR algorithm has been tested against simulated and experimental X‐ray diffraction computed tomography data using the TOPAS software.